Exploding Stars, Dead Dinosaurs, and Zombies : Youth Ministry in the Age of Science - Root, Andrew, 1974- (Theology for the people., 2018)
Many things threaten the faith of youth today, but none more than science. The commitments of science and Christianity seem to be at odds science makes truth claims based on experiments and proofs, while religion asks for belief and trust. But Andrew Root demonstrates that, in fact, the two are not incompatible. Root, a renowned expert on adolescent spirituality, shows how science overstates its claims on truth, while faith often understates its own claims. Both faith and science frame the experience and reality of teenagers, and both have something valuable to offer as adolescents develop. Drawing on a fictional account of a youth pastor and the various students he encounters, Root paints a compelling picture of how faith can flourish, even in our scientific age.